Humanitas jako ćwiczenie duchowe. Rozważania nad egzystencjalnym wymiarem humanizmu Cycerona - Kurowicki, Jan (Colloquia Litteraria, 2022)
The article took up the issue of the Ciceronian understanding of the category humanitas understood as an example of spiritual exercise. The historical context of Cicero’s inspiration was discussed first. In the following part of the paper, the notion of humanitas was subjected to a semantic analysis, which demonstrates several concepts used by Cycero to describe this phenomenon in his writings. Then, the discussed issue was interpreted in the key of the theory proposed by Pierre Hadot and Juliusz Domański, according to which the ancient philosophy was a kind of spiritual exercise (exercice spirituel). Based on the analysis of selected passages from Cicero’s work De officiis, an attempt was made to demonstrate the relevance of Hadot’s theory to Cicero’s concept.